Effects of Cutting Parameters and Point Angle on Thrust Force and Delamination in Drilling of CFRP - Yardimeden, Ahmet; Kilickap, Erol; Celik, Yahya Hisman (Carl Hanser Verlag, 2014)
Parts made of composite materials are generally produced by near-net-shape technology. However, additional machining operations such as drilling are often required to facilitate components assembling. Drilling of composite materials is also a common process in the assembly of aerospace and automotive composite structures. During drilling, unlike the conventional materials, a few damage forms may take place. Among these damage forms, the delamination is the most important one. Therefore, the experimental studies carried out on drilling of CFRP composite materials for determining optimum processing parameters are of great importance. In this particular study, delamination in CFRP composites caused by drilling was investigated. The composite material was drilled under various spindle speeds, feed rates and drill point angles. The results showed that delamination and thrust forces were affected by cutting parameters. It was demonstrated that feed rate and drill point angle make the largest contribution to the overall performance.
Keywords: Materials testing; drilling; delamination; CFRP; thrust force